Gilead - Robinson, Marilynne (Virago, 2004)
Reverend John Ames is dying in 1956 in Gilead, Iowa, and he is recording his family’s story. Glory Boughton has returned to care for her dying father and soon her brother, Jack, the prodigal son, comes home, too.